Knowledge, attitudes and practices of healthcare workers about healthcare waste management at a district hospital in KwaZulu-Natal - Adekunle Olaifa; Romona D. Govender; Andrew J. Ross (South African Family Practice)
Background: Healthcare generates a large amount of healthcare waste (HCW), which is complex to manage because of its variety and potential to create health and safety hazards if improperly handled. It is essential that healthcare workers have appropriate knowledge of and adhere to proper disposal methods for each category of HCW. Aim: The aim of this study was to assess the knowledge, attitudes and practices of staff working at a district hospital about HCW management, and measure associations between these variables. Setting: The setting for this study was a district hospital in KwaZulu-Natal province. Methods: This was an observational descriptive study among 241 professional and non-professional staff. Data were collected using a questionnaire and analysed using the Statistical Package for the Social Sciences. Results: Knowledge of HCW management was generally inadequate, with 42.7% of the participants scoring ‘poor’ overall. Just over half of the participants reported a good attitude towards the appropriate disposal of HCW but only 53.9% demonstrated good HCW management practices. There was a significant (p 0.05) relationship between knowledge and practice and between attitudes and practices (p 0.05). Conclusion: Appropriate training and supervision in HCW management as well as relevant and ongoing in-service training is needed to ensure appropriate knowledge, attitudes and safe practice among all members of staff. As poor practices have been reported on a number of occasions from different hospitals in South Africa, relevant training must also be introduced or improved at undergraduate level.